Associations between Motor Competence, Physical Activity and Sedentary Behaviour among Early School-Aged Children in the SELMA Cohort Study - Johanna Delvert; Heléne V. Wadensjö; Carl-Gustaf Bornehag; Sverre Wikström (MDPI AG, 2024)
Low motor competence (MC) has been associated with lower physical activity (PA) and long-term health risks in children. Less is known about sex-specific patterns and associations during early school age. The aim of this study was to explore how motor difficulties are associated with PA levels, screen time, and organised sports participation (OSP). Data from 479 children, seven years of age, participating in the Swedish Environmental, Longitudinal, Mother and child, Asthma, and allergy (SELMA) pregnancy cohort study were used. MC and activity-related outcomes were assessed with questionnaires answered by parents. Associations between MC and outcomes were evaluated using logistic regression models adjusted for sex, overweight, and parental education level. Sex differences were investigated with interaction analyses and in stratified models. Children with motor difficulties had the same level of PA as their peers, but more screen time and lower OSP. Compared with children with normal MC, boys with motor difficulties had lower rates of OSP, but girls did not. This indicates that the identification and compensatory support for motor difficulties for boys at an early age, as well as the development of inclusive leisure time activities, are of importance to facilitate health-promoting activities on equal terms.